Political finance: Checks and abuses. Current problems and new developments. - Arnim, Hans Herbert von (My University, 2003)
Der Beitrag gibt ausgehend vom deutschen Modell einen Überblick über die Art und Weise der Finanzierung einer Partei: durch Mitgliedsbeiträge, Spenden, durch Kapitaleinkünfte aus Parteienbesitz, durch direkte und indirekte öffentliche Zuwendungen. Der Autor stellt Überlegungen zur Notwendigkeit einer Parteienfinanzierung an und erläutert die Missbrauchsmöglichkeiten. Deren Kontrolle und ein mögliches Gegengewicht liegt beim Verfassungsgericht, bei der Öffentlichkeit, in Wahlen, durch Regierungen und in der Existenz von Zwei-Kammern-Systemen.

This contribution explores some fundamental aspects of political finance as well as some issues of immediate interest. Departing from the German perspective, the author also takes several other countries into consideration. Besides, he looks at public subsidies for European political parties as well as the planned Statute for Members of the European Parliament. The author decided to take Germany as a starting point as this country ranks as the embodiment of the party state. It is not by pure chance that Germany was the first European state to introduce state financing of political parties, which slowly led to its acceptability in other countries. On the one hand, "pioneering" in the field of state finance for political parties gave early rise to dangers of excessive public subsidies for political parties in Germany. On the other hand, the German Constitutional Court has the jurisdiction to counteract decisions made by the parliament for its own benefit. In a long struggle against the legislative influence exercised by the treasurers of the political parties, the German Constitutional Court, from its relatively removed position, monitored the matter very carefully and tried to develop reasonable regulations and limits regarding public subsidies for political parties.
Keywords: Partei; Vergütung; Finanzen; Besitz; Subvention; Forschungsprojekt; Parteienfinanzierung; Kontrolle; Mitgliedsbeitrag; Spende; Parteispende